(untitled) (Bollettino di zoologia agraria e bachicoltura, 2024)
The genus Pantecphylus Karsch, 1891 (Orthopteroidea, Ensifera,Tettigonoidea, Pseudophyllidae) is widely distributed in Central Africa. During the last century, more than hundred specimens were collected and preserved in European museums, but not further studied. Most of them were designated as P. cerambycinus Karsch, 1891. Taxonomical studies of the material, stored in the collections of Bruxelles and Tervuren, discriminated six new species, found near to, and North of the Equator by comparing several characters, as shape of fastigium ertices, supra-anal plate, cerci, styli, and structure of the male subgenital plate. According to the site of collection, the species were named P. bambesai, P. banguensis, P. banzyvillei, P. congoensis, P. aequatori, and P. sudanensis. In two cases, the holotype was the only known one. Several females could not be attached to one of the species. For males, a key to the species was presented.